Dendritic cells can effectively be pulsed by HBVsvp and induce specific immune reactions in mice - Farag, Mohamed Mansour Saad; Hoyler, Birgit; Encke, Jens; Stremmel, Wolfgang; Weigand, Kilian (Vaccine, 2010)
Eradication of chronic Hepatitis B virus (HBV) infection, marked by HBs seroconversion, is very rarely achieved by treatment with nucleoside and nucleotide analogs. Therapeutic cell based approaches, like interferon therapy, have a higher chance of seroconversion. Dendritic cells (DC) are key players in the cellular immune response and have been shown to play an important role in controlling HBV infection. In this study, the potential of ex vivo activated DC to induce specific immune responses against HBV was examined. DC derived from bone-marrow of BALB/c or C56BL/6 mice were pulsed with HBV subviral particles (HBVsvp), derived from the HepG2.2.15 cell line. HepG2.2.15 produces subviral particles consisting of the HBc and HBs proteins. Thus, the entire “viral surface” is presented to DC to induce an immune reaction. In vitro pulsation with HBVsvp successfully activated bone-marrow derived DC, demonstrated by FACS analysis showing increased MHCII, CD 86 and CCR-7. Immunization of mice, via subcutaneous injection of the activated DC, induced HBV specific immune reactions which were measured by ELISA, ELISPOT and T-cell proliferation analysis. Vaccination with ex vivo activated DC may be a promising tool for therapeutic or prophylactic approaches against the Hepatitis B virus.